Analisis Hukum Humaniter Internasional Terhadap Penyerangan Dual Use Object Dalam Konflik Bersenjata Rusia Dan Ukraina - Azzahra, Nadia; Hastuti, Lina (Jurist-Diction, 2025)
International Humanitarian Law distinguishes between civilian and military objects in armed conflicts. However, complexity arises with dual-use objects. In the Russia-Ukraine conflict, attacks on Ukraine's energy infrastructure by Russia and the Kerch Strait Bridge by Ukraine raise legal questions. This research explores the status of dual-use objects and the legality of such attacks. Despite the absence of definite rules, some experts view them as potential military targets. Analysis indicates that Ukraine's energy infrastructure could be considered military, but Russia's attacks are deemed in violation of International Humanitarian Law. Conversely, the Kerch Strait Bridge cannot be categorized as a military object, making attacks against it a breach of international law. The importance of considering indirect impacts of attacks is also emphasized.